Invasive Fascioloides magna infections impact gut microbiota in a definitive host in Europe - Fleischer, Ramona; Velling, Marc; Peters, Wibke; Peterka, Tomáš; Franke, Frederik; Vymyslická, Pavla Jůnková; Rehbein, Steffen; Heurich, Marco; Sommer, Simone (International journal for parasitology. Parasites and wildlife, 2024)
Invasive parasites that expand their natural range can be a threat to wildlife biodiversity and may pose a health risk to non-adapted, naive host species. The invasive giant liver fluke, Fascioloides magna, native to North America, has extended its range in Europe and uses mainly red deer (Cervus elaphus) as definitive hosts. The penetration of the intestinal barrier by the young flukes to reach the liver via the abdominal cavity as well as the release of fluke metabolism products and excreta with the bile and/or changes in the microbial community of the biliary system may enable the translocation of intestinal bacteria across the intestinal barrier and, in turn, could be associated with inflammation and changes in the intestinal bacterial community. The gut commensal community plays a key role in host nutrition and interacts with cells of the immune system to maintain host health. For this study, the gut bacterial community of red deer infected with F. magna and of non-infected red deer from one of the largest forest ecosystems in Central Europe, located on the border between the Czech Republic and Germany, was investigated. The individual fluke burden was associated with changes in the gut microbial composition of the gut of infected individuals, whereas the diversity and composition of the gut bacteria were only slightly different between fluke-infected and uninfected deer. Several bacterial taxa at the genus level were unique to individuals carrying either one or many liver flukes. Our results suggest that the microbiota of red deer is stable to perturbation by low numbers of F. magna. However, a larger parasite burden may cause changes in the gut microbial composition in definitive hosts implying that non-invasive fecal microbiome assessments could serve as indicator for wildlife health monitoring.
Keywords: Wildlife health monitoring; Bohemian forest ecosystem; Gut microbiota; Invasive parasite; Liver fluke Fascioloides magna